IDENTIFIKASI KETERLAMBATAN PEKERJAAN PEMBANGUNAN GEDUNG KULIAH S (SBSN) UIN SJECH M. DJAMIL DJAMBEK BUKITTINGGI - Ridho Alfariz, Muhammad; Eka Priana, Surya; Hafnil, Jon (Ensiklopedia Research and Community Service Review, 2024)
During project implementation, several obstacles occurred, one of which was work delays. Delays in construction projects can be interpreted as failure to meet the completion time for construction work as stated in the contract. This research aims to determine the use of the concept of the Fault Tree Analysis (FTA) method and to determine the control and causes of delays on projects. The results of the research show that the work that experienced delays in the UIN Sjech M. Djamil Djambek Bukittinggi Lecture Building (SBSN) construction project was work in weeks 2, 11, 12, 13, and 21. This was also influenced by several things such as weather factors. , lack of workers, lack of experts, ordering materials that are difficult to obtain, delays in architectural work, and inefficient division of labor. The conclusion of this research is to pay attention to delay factors in construction implementation to anticipate possible delays.Keywords: Delay; Project; Fault Tree Analysis; Controlling.